KERAGAMAN MORFOLOGI Hoya purpureofusca Hook.f. ASAL TAMAN NASIONAL GUNUNG GEDE PANGRANGO - Rahayu, Sri; Tyas, Kartika Ning; Wawangningrum, Hary (BERITA BIOLOGI, 2019)
Hoya purpureofusca Hook.f. (Apocynaceae: Asclepiadoideae) has been used as an ornamental plant and the international trade of this species has become increasing. This species has restricted distribution on the high elevation of Java and Bali mountains. This epiphyte climber has succulent leaves and umbellate delicate flowers. Flower has star shape, succulent and waxy, purple., c.1 cm in diameter. The observation on the morphological characteristic is aimed to select the best sample for ornamental plant. The total of 17 observed samples were obtained from three populations at Gunung Gede Pangrango National Park, West Java, Indonesia. The selection was based on the node length, size of the leaves, and flower number, size and color. The result showed that P01 from Cibodas could be developed as leaf ornamental plant, because its shortest node and small leaves. SP1 from Selabintana could be developed as flower ornamental plant, it has numerous, larger and deep purple flower. SP1 and P01 have the farest relatives distance among all observed accessions, but still have a similarity of 75%.